Effect of inspiratory muscle training on dyspnea-related kinesiophobia in chronic obstructive pulmonary disease: A randomized controlled trial. (August 2021) - Saka, Seda; Gurses, Hulya Nilgun; Bayram, Mehmet
Abstract: Background: The major symptom of chronic obstructive pulmonary disease (COPD) is dyspnea, which causes dyspnea-related kinesiophobia resulting in avoidance of activities associated with dyspnea or compensation by reducing the rate of activity. The aim of this study was to assess dyspnea-related kinesiophobia and determine the effect of inspiratory muscle training (IMT) on dyspnea-related kinesiophobia in COPD. Methods: Forty COPD subjects were randomly allocated to either the IMT or sham group. Both groups' maximal inspiratory pressure (MIP) was assessed weekly. All patients were instructed to perform the training exercises for 15 min twice a day, 5 days a week for a total of 8 weeks. In the IMT group, intensity was set at 30% of MIP and adjusted according to weekly MIP value. In the sham group, intensity remained constant at 15% of initial MIP. Pulmonary function test (PFT), respiratory muscle strength, 6-min walk test (6 MWT), Breathlessness Beliefs Questionnaire (BBQ), Modified Medical Research Council scale (MMRC), modified Borg scale, Hospital Anxiety and Depression Scale (HADS), Saint George's Respiratory Questionnaire (SGRQ), and COPD Assessment Test (CAT) were assessed before and after the intervention. Results: BBQ scores ranged from 18 to 51, with mean values in the IMT and sham groups of 39.80 ± 7.62 and 43.00 ± 6.58, respectively. When between-group differences of all outcome scores were compared, there was a statistically significant improvement in the IMT group than in the sham group (p < 0.05). After IMT, statistically significant decreases in BBQ and modified Borg scores were observed in within groups (p ≤ 0.001). These decreases were significantly greater in the IMT group (p ≤ 0.001). MMRC decreased significantly only in the IMT group (p < 0.001). There was a statistically significant increase in PFT values in the IMT group (p = 0.007–0.045), but no difference in the sham group (p = 0.129–0.886). Both groups showed statistically significant improvement in respiratory muscle strength, 6 MWT distance, and CAT score after 8 weeks (p < 0.05). All HADS and SGRQ scores decreased significantly in the IMT group (p < 0.001), whereas only the SGRQ activity score decreased significantly in the sham group (p = 0.017). Conclusions: Our study provides data on the presence and level of dyspnea-related kinesiophobia in COPD patients. All patients had BBQ scores higher than 11, indicating dyspnea-related kinesiophobia. IMT reduced BBQ score and improved respiratory function, and exercise capacity. Our results also support the other known benefits of IMT such as reduced dyspnea and symptom perception, decreased anxiety and depression, and improved quality of life. Highlights: Dyspnea related kinesiophobia is present in COPD subjects. Eight weeks of inspiratory muscle training significantly decrease the dyspnea related kinesiophobia. . Other known benefits of inspiratory muscle training are supported with this current study. .